A Comparison of General Price Level and Historical Cost Financial Statements in the Prediction of Bankruptcy: A Reply. - Norton, Curtis L.; Smith, Ralph E. (The Accounting Review, 1980)
The article presents reply by authors to comments by I. Solomon and P.J. Beck, in a paper titled "A Comparison of General Price Level and Historical Cost Financial Statements in the Prediction of Bankruptcy: A Comment," published in the July 1980 issue of the journal "The Accounting Review." According to authors, Solmon and Beck correctly indicated that other uses of general price level (GPL) information must be examined. Perhaps the focus of future research should be to determine whether GPL information is useful in assisting investors and creditors in predicting future cash flows in light of FASB's current focus. However, Solmon and Beck failed to illustrate that conclusion of authors of the present article related to GPL and HC "does not actually follow from the analysis and results." Authors also did not prove any serious deficiencies in the methodology used to reach those results. Authors of the article continue to contend that if the criterion of usefulness is the ability to predict bankruptcy, their study showed that GPL financial statements are equally useful as, but not more useful than, HC financial statements.